VENTILATORY EQUIVALENT FOR OXYGEN DISTINGUISHES BETWEEN PASSING AND FAILING A SPONTANEOUS BREATHING TRIAL BEFORE EXTUBATION...Canadian Society of Respiratory Therapists Annual Conference (Virtual), May 5-7, 2021 - Ellens, T.; Kaur, R.; Roehl, K.; Dubosky, M.; Vines., D. L. (Canadian Journal of Respiratory Therapy, 2021)
Introduction: Weaning predictors can help liberate patients in a timely manner from mechanical ventilation. Ventilatory equivalent for oxygen (VEqO2), a surrogate for work of breathing and a measure of the efficiency of breathing, may be an important noninvasive alternative to other weaning predictors. Our study's purpose was to observe any differences in VEqO2 between extubation outcome groups. Methods: Employing a metabolic cart, oxygen consumption (...O2), minute volume (VE), tidal volume (VT), and breathing frequency were recorded during a spontaneous breathing trial (SBT) to calculate VEqO2 and the rapid shallow breathing index (RSBI) in 34 adult participants in the intensive care unit. Five-breath means of VEqO2 and the RSBI collected throughout the SBT were examined between SBT pass and fail groups and extubation pass and fail groups using the Mann-Whitney U test with P < 0.05. Results: Data from 31 participants were analyzed between SBT outcome groups. Data from 20 participants were examined for extubation outcome after a successful SBT. Median (interquartile range) VEqO2 was not different between extubation groups. Participants who passed the SBT had a higher median VEqO2 than those who did not at the midpoint (25.3 L/L ...O2 [22-33L/L ...O2] vs. 23.7 L/L ...O2 [18-24 L/L ...O2], P = 0.035) and at the end (25.5 L/L ...O2 [23-34 L/L ...O2] vs. 21.3 L/L ...O2 [20-24 L/L ...O2], P = 0.017) of the SBT. Discussion: VEqO2 may show differences in SBT outcomes, but not differences between extubation outcomes. VEqO2 may be able to detect differences in work during an SBT but may not be able to predict change in workload in the respiratory system after extubation. The small sample size may also have prevented any differences in extubation outcomes to be shown. Conclusion: VEqO2 was higher in patients that passed their SBT. VEqO2 was not useful in identifying extubation success or failure in adult mechanically ventilated patients.